High-Fat Diet-Induced Obesity Model Does Not Promote Endothelial Dysfunction via Increasing Leptin/Akt/eNOS Signaling - Rocha, Vanessa da Silva; Claudio, Erick Roberto Gonçalves; da Silva, Vitor Loureiro; Cordeiro, Jóctan Pimentel; Domingos, Lucas Furtado; da Cunha, Márcia Regina Holanda; Mauad, Helder; Nascimento, Thiago Bruder do; Lima-Leopoldo, Ana Paula; Leopoldo, André Soares (Frontiers in Physiology, 2019)
Experimental studies show that the unsaturated high-fat diet-induced obesity promotes vascular alterations characterized by improving endothelial L-arginine/Nitric Oxide (NO) pathway. Leptin seems to be involved in this process, promoting vasodilation via increasing NO bioavailability. We investigated the involvement of leptin on vascular reactivity in aortic rings of obese rats. Furthermore, to test the hypothesis that the improvement at vasodilator response observed in obesity induced by high-fat diet rich in unsaturated fatty occurs mainly due an increase in the circulating leptin, which triggers vascular leptin signaling promoting Akt and NO activation. Thirty-day-old male Wistar rats were randomized into two groups: control (C) and obese (Ob). The group C was fed with a standard diet and the group Ob was alternately submitted to unsaturated high-fat diet for 27 weeks. Adiposity, hormonal and biochemical parameters, and systolic blood pressure were also performed. Concentration response curves were performed to leptin or acetylcholine in presence or not of Akt and NOS inhibitor. Our results show that unsaturated high-fat diet promoted greater feed efficiency, elevation of body weight and body fat, adiposity index characterizing a model of obesity. However, comorbidities frequently associated with experimental obesity were not visualized, such as glucose intolerance, dyslipidemia and hypertension. The evaluation of the endothelium-dependent relaxation with acetylcholine showed no differences between the C and Ob rats. After NOS inhibition, the response was completely abolished in the Ob group, but not in the C group. Furthermore, Akt inhibition completely blunted the vascular relaxation in the C group, but no in the Ob group. Ob group was more sensitive to leptin-induced vascular relaxation; L-NAME incubation abolished the relaxation in both groups at the same level. Although Akt inhibitor pre-incubation reduced the leptin response, group C was more sensitive to its effect. In summary, the obesity induced by an unsaturated high-fat diet for 27 weeks does not change the vascular reactivity due to a higher basal NO production, possibly because of the higher plasmatic leptin concentration. However, the increase in NO production occurs partially by the increase in NOS activation mediated by the Akt pathway.